Cement composition and hardened product

The cement composition, enriched with rapid hardwoods and other additives, addresses the challenges of filling narrow gaps and developing strength within one hour, offering improved handling time and durability.

JP7674118B2Active Publication Date: 2025-05-09DENKA CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021039450
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-11
Publication Date
2025-05-09
Estimated Expiration
2041-03-11

AI Technical Summary

Technical Problem

Existing ultra-fast hardening, high-flow cement compositions struggle to fill narrow gaps without leaving gaps, require excessive working time, and fail to develop practical strength within one hour while being durable.

Method used

A cement composition incorporating specific additives such as rapid hardwoods, silica fumes, fibers, clay minerals, thickeners, foaming agents, water reducing agents, and condensation adjusters, which enhance filling properties, working time, strength development, and crack resistance.

Benefits of technology

The cement composition effectively fills narrow gaps without leaving gaps, provides a moderate working time, achieves excellent strength at a young age, and reduces cracking, thereby meeting the demands for streamlined construction and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007674118000001
    Figure 0007674118000001
  • Figure 0007674118000002
    Figure 0007674118000002
Patent Text Reader

Abstract

To provide a cement composition that can fill a narrow clearance without any gap, has an adequate pot life, expresses excellent strength at a young material age, and also resists cracking.SOLUTION: A cement composition contains cement, a quick-hardening material, silica fume, a fiber, clay mineral, a thickener, a foamer, a water-reducing agent, and a setting modifier. A content of the quick-hardening material is 10 pts.mass or more and 50 pts.mass or less relative to 100 pts.mass of the cement. A content of the setting modifier is 0.1 pt.mass or more and 2 pts.mass or less relative to 100 pts.mass of the cement. The quick-hardening material is a mixture of calcium aluminate and gypsum. Relative to 100 pts.mass of calcium aluminate, the gypsum is 50-200 pts.mass.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cement composition and a hardened product, and more particularly to an ultra-fast-hardening, high-fluidity cement composition that is used mainly in the civil engineering and construction industries. [Background technology]

[0002] In the fields of civil engineering and architecture, there is an increasing demand for streamlined construction, and materials that can be put into service quickly are required. For example, an example of an ultra-fast hardening material is a cement-based material that is ultra-fast hardening and has excellent fluidity (see Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2007-145652 A Summary of the Invention [Problem to be solved by the invention]

[0004] The ultra-rapid-hardening, high-fluidity cement composition proposed in Patent Document 1 contains Portland cement, calcium aluminate, anhydrous gypsum, calcium hydroxide, lithium carbonate, an alkali metal carbonate other than lithium carbonate, an organic acid, a fluidizing agent, and a gas foaming substance, and is an ultra-rapid-hardening, high-fluidity cement composition that has excellent fluidity, can suppress the occurrence of settlement (material separation), ensures sufficient pot life, and has little temperature dependency of strength development. However, in recent years, the demand for more streamlined construction and the need to meet new needs have led to an increasing demand for ultra-fast hardening materials. Specifically, there is a demand for cement-based materials that can fill narrow gaps and have high self-leveling properties after filling, allowing them to fill gaps without gaps. In addition, there is a demand for cement-based materials that have a moderate working time so as not to require excessive working time while ensuring working time for ease of handling, that can demonstrate practical strength from one hour after hardening, and that also have excellent durability. Therefore, an object of the present invention is to provide a cement composition which can be filled into narrow gaps without leaving any gaps, has an appropriate working life, is excellent in strength development at an early age, and can also reduce cracks. [Means for solving the problem]

[0005] The present inventors have conducted intensive research to solve the above problems, and have discovered that the inclusion of specific hardening agents, silica fume, fibers, clay minerals, thickeners, foaming agents, water reducing agents, and setting regulators results in high filling properties, a suitable working life, improved strength at an early age, and crack resistance, and have thus completed the present invention. That is, the present invention is as follows. [1] A cement composition containing cement, a hardening agent, silica fume, fiber, a clay mineral, a thickener, a foaming agent, a water reducing agent, and a setting regulator, wherein the content of the hardening agent is 10 parts by mass or more and 50 parts by mass or less per 100 parts by mass of the cement, and the content of the setting regulator is 0.1 parts by mass or more and 2 parts by mass or less per 100 parts by mass of the cement, and the hardening agent contains calcium aluminate and gypsum, and the amount of the gypsum is 50 to 200 parts by mass per 100 parts by mass of the calcium aluminate. [2] The cement composition according to [1] above, wherein the content of the silica fume is 1 part by mass or more and 10 parts by mass or less per 100 parts by mass of the cement. [3] The cement composition according to [1] or [2] above, wherein the fibers are vinylon fibers. [4] The cement composition according to any one of the above [1] to [3], wherein the content of the fibers is 0.02 parts by mass or more and 0.2 parts by mass or less per 100 parts by mass of the cement. [5] The cement composition according to any one of the above [1] to [4], wherein the content of the clay mineral is 0.05 parts by mass or more and 0.3 parts by mass or less per 100 parts by mass of the cement. [6] The cement composition according to any one of the above [1] to [5], wherein the content of the thickener is 0.01 part by mass or more and 0.1 part by mass or less per 100 parts by mass of the cement. [7] The cement composition according to any one of the above [1] to [6], wherein the content of the foaming agent is 0.001 part by mass or more and 0.01 part by mass or less per 100 parts by mass of the cement. [8] The cement composition according to any one of the above [1] to [7], wherein the content of the water reducing agent is 0.1 part by mass or more and 1 part by mass or less per 100 parts by mass of the cement. [9] A hardened body obtained by using the cement composition according to any one of the above [1] to [8]. Effect of the Invention

[0006] According to the present invention, it is possible to provide a cement composition which can be filled into narrow gaps without leaving any gaps, has an appropriate pot life, is excellent in strength development at an early age, and can also reduce cracks. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The present invention will be described in detail below. [Cement composition] The cement composition of the present invention contains cement, a hardening agent, silica fume, fiber, a clay mineral, a thickener, a foaming agent, a water reducing agent, and a set adjuster.

[0008] <Cement> The cement is not particularly limited, and examples thereof include various Portland cements such as ordinary, early strength, extra early strength, low heat, moderate heat, and sulfate resistant Portland cements, various blended cements obtained by mixing Portland cements with blast furnace slag, fly ash, silica, or limestone powder, and waste-recycled cements, so-called ecocement. The content of cement in the cement composition is not particularly limited, but is usually 50 to 98 mass%, preferably 55 to 95 mass%, and more preferably 60 to 92 mass%. If it is equal to or more than the lower limit, the hardened product can exhibit sufficient strength. On the other hand, if it is equal to or less than the upper limit, the content of the hardening agent etc. becomes sufficient, the occurrence of fluidity and subsidence can be suppressed, and sufficient usable time can be ensured.

[0009] <Sudden hardwood> The hardening agent used in the present invention contains calcium aluminate and gypsum.

[0010] (Calcium Aluminate) The calcium aluminate of the present invention is a general term for compounds mainly composed of CaO and Al2O3. In the present invention, it is preferable to use calcium aluminate having a CaO / Al2O3 molar ratio of 0.5 to 3.0. When the CaO / Al2O3 molar ratio is 0.5 or more, sufficient strength is exhibited, and when the CaO / Al2O3 molar ratio is 3.0 or less, sufficient fluidity and usable life are obtained. From the above viewpoints, the CaO / Al2O3 molar ratio is more preferably in the range of 0.75 to 2.5, and even more preferably in the range of 1.0 to 2.0. Specific examples of calcium aluminates include crystalline calcium aluminates such as CaO·2Al2O3, CaO·Al2O3, 12CaO·7Al2O3, 11CaO·7Al2O3·CaF2, and 3CaO·3Al2O3·CaSO4, as well as amorphous compounds whose main components are CaO and Al2O3.

[0011] Calcium aluminate can be obtained by heat treating CaO raw materials and Al2O3 raw materials in a rotary kiln, electric furnace, or the like. Examples of CaO raw materials for producing calcium aluminate include calcium carbonate such as limestone or shells, calcium hydroxide such as slaked lime, and calcium oxide such as quicklime. Examples of Al2O3 raw materials include industrial by-products such as bauxite and aluminum ash, as well as aluminum powder.

[0012] When calcium aluminate is obtained industrially, it may contain impurities. Specific examples of impurities include SiO2, Fe2O3, MgO, TiO2, MnO, Na2O, KO, Li2O, S, PO5, and F. The presence of these impurities is not particularly problematic as long as they do not substantially impede the object of the present invention. Specifically, it is not particularly problematic when the total amount of these impurities is 10 mass% or less.

[0013] The particle size of the calcium aluminate of the present invention is not particularly limited, but is preferably 3000 to 9000 cm in terms of Blaine specific surface area value (hereinafter sometimes referred to as "Blaine value"). 2 / g. The Blaine value is preferably in the range of 3000 cm 2 / g or more, sufficient strength is exhibited and the 9000 cm 2 If the Blaine value is less than 4000 cm / g, the fluidity and working life can be secured. 2 It is more preferable that the range is / g.

[0014] (plaster) The gypsum used in the present invention is a general term for minerals whose main component is calcium sulfate, including anhydrous gypsum (CaSO4), hemihydrate gypsum (CaSO4·1 / 2H2O), and dihydrate gypsum (CaSO4·2H2O). In the present invention, it is preferable to use anhydrous gypsum in order to ensure sufficient strength and pot life. The anhydrous gypsum is not particularly limited, but it is preferable to use type II anhydrous gypsum, and among them, it is preferable to use acidic anhydrous gypsum with a pH of 4.5 or less, because it is easy to ensure a pot life and the subsequent strength increase is good. Here, the pH of anhydrous gypsum means the pH of the supernatant liquid when 1 g of anhydrous gypsum is added to 100 cc of pure water and stirred. The particle size of the gypsum in the present invention is 3000 to 9000 cm in Blaine value. 2 / g, and 4000 to 8000 cm 2 By making the particle size approximately the same as that of the calcium aluminate, it becomes easy to uniformly mix the calcium aluminate and anhydrous gypsum.

[0015] (Mixing ratio of calcium aluminate and gypsum) The mixing ratio of calcium aluminate and gypsum is 50 to 200 parts by mass of gypsum per 100 parts by mass of calcium aluminate. When the content of gypsum is within the above range, the pot life of concrete is easily ensured, and the initial strength is sufficiently developed. From the above viewpoints, the content of gypsum is preferably in the range of 60 to 200 parts by mass, more preferably in the range of 70 to 150 parts by mass, per 100 parts by mass of calcium aluminate.

[0016] (Grain size of quick hardening material) The grain size of the hardening material is not particularly limited, but is preferably 3000 to 9000 cm in Blaine value. 2 / g. 2 / g or more, sufficient initial strength is exhibited and the 9000 cm 2 From the above viewpoints, the particle size of the hardening agent is 4000 to 8000 cm in Blaine value. 2 It is more preferable that the range is / g.

[0017] (Accelerated hardening material content) The content of the hardening agent is 10 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of cement. If the content of the hardening agent is less than 10 parts by mass, the hardening speed becomes insufficient, and if it exceeds 50 parts by mass, the strength at long age decreases. From the above viewpoints, the content of the hardening agent is more preferably 20 parts by mass or more and 45 parts by mass or less, and even more preferably 25 parts by mass or more and 40 parts by mass or less relative to 100 parts by mass of cement.

[0018] <Silica fume> The cement composition of the present invention contains silica fume. Silica fume, as specified by JIS A 6207, is a spherical ultrafine particle composed mainly of amorphous silicon dioxide, which is collected from the exhaust gas generated when producing metal silicon or ferrosilicon in an arc furnace. In addition to the above, the silica fume can be produced by adjusting the heat treatment conditions of the raw material and setting the collection temperature to 550°C or higher in a method of oxidizing metal silicon fine powder in a flame or a method of melting siliceous raw material fine powder in a high-temperature flame. In some cases, the silica fume is produced by collecting the zircon sand in a cyclone or the like when the zircon sand is electrofused in an electric furnace, and then classifying the collected particles. The average particle size of the silica fume is 1 μm or less.

[0019] In the present invention, it is preferable to use so-called zirconia-derived silica fume, which is produced by electromelting zircon sand in an electric furnace, collecting the resulting material using a cyclone or the like, and then classifying it. Zirconia-derived silica fume is a by-product of manufacturing electrofused zirconia (zirconium oxide ZrO2) used in refractories, polishing and grinding materials, electronic materials, ceramic pigments, etc., and is made by collecting exhaust gas generated when zircon sand (ZrSiO4) is electrofused at, for example, 2200°C. From the viewpoint of fluidity and strength development, the preferred specific surface area of ​​zirconia-derived silica fume is 5 to 13 m2 in terms of BET specific surface area. 2 / g, and 8 to 12m 2 It is more preferable that the molecular weight is / g. Furthermore, the average particle size of zirconia-derived silica fume is larger than that of conventional silica fume collected from exhaust gas generated when producing metallic silicon or ferrosilicon in an arc furnace, which is 0.1 to 0.3 μm, and is preferably about 1 μm or less.

[0020] In the cement composition of the present invention, good fluidity can be ensured by containing silica fume. The content of silica fume is preferably 1 part by mass or more and 10 parts by mass or less per 100 parts by mass of cement. When it is 1 part by mass or more, good fluidity is easily obtained, and when it is 10 parts by mass or less, it is possible to prevent the viscosity from increasing and the fluidity from becoming poor. From the above viewpoints, the content of silica fume is more preferably 2 parts by mass or more and 7 parts by mass or less, and further preferably 3 parts by mass or more and 6 parts by mass or less, per 100 parts by mass of cement.

[0021] <Textile> The cement composition of the present invention contains fibers. By containing fibers of a certain size, it is possible to improve crack resistance. The fibers are not particularly limited, and examples thereof include synthetic fibers and inorganic fibers. Examples of synthetic fibers include vinylon fibers, polyethylene fibers, polypropylene fibers, polyacrylic fibers, cellulose fibers, polyamide fibers, pulp, hemp, wood wool, and wood chips. Of these, vinylon fibers are preferred. Examples of inorganic fibers include steel fibers, glass fibers, and carbon fibers, with steel fibers being preferred among these.

[0022] The average fiber diameter of the fibers is preferably in the range of 10 μm to 2 mm. When the average fiber diameter is 10 μm or more, good crack resistance is obtained, and when it is 2 mm or less, the mortar material does not separate. From the above viewpoints, the average fiber diameter of the fibers is more preferably 50 μm to 1.5 mm, and further preferably 100 μm to 1 mm. The average fiber length of the fibers is preferably in the range of 1 mm to 20 mm. When the average fiber length is 1 mm or more, good crack resistance is obtained, and when it is 20 mm or less, the filling property of the material is not hindered. From the above viewpoints, the average fiber length of the fibers is more preferably 3 to 15 mm, and further preferably 4 to 8 mm.

[0023] The content of the fiber in the cement composition of the present invention is preferably 0.02 parts by mass or more and 0.2 parts by mass or less relative to 100 parts by mass of cement. When the content of the fiber is 0.02 parts by mass or more, good crack resistance is obtained, and when the content of the fiber is 0.2 parts by mass or less, the fluidity of the cement composition is not reduced. From the above viewpoints, the content of the fiber is more preferably 0.03 parts by mass or more and 0.18 parts by mass or less, and even more preferably 0.05 parts by mass or more and 0.15 parts by mass or less relative to 100 parts by mass of cement.

[0024] <Clay minerals> The cement composition of the present invention contains a clay mineral. By containing a clay mineral, bleeding is suppressed. The clay mineral is not particularly limited, and examples thereof include bentonite, montmorillonite, kaolin, sepiolite, saponite, mica, palygorskite (attapulgite), etc. These can be used in the form of natural products, synthetic products, or processed products. Among these clay minerals, bentonite, which has a high bleeding suppression effect, is preferred. Moreover, the ion exchange equivalent is preferably 10 milliequivalents or more per 100 g, and the aspect ratio is preferably 50 to 5000. The aspect ratio here is the length / thickness ratio of the clay mineral dispersed in layers, determined from an electron microscope photograph.

[0025] The content of the clay mineral in the cement composition of the present invention is preferably 0.05 parts by mass or more and 0.3 parts by mass or less relative to 100 parts by mass of cement. If the content of the clay mineral is 0.05 parts by mass or more, bleeding is suppressed, and if it is 0.3 parts by mass or less, the flow value does not decrease. From the above viewpoint, the content of the clay mineral is more preferably 0.1 parts by mass or more and 0.2 parts by mass or less relative to 100 parts by mass of cement.

[0026] <Thickener> Thickeners adjust the viscosity of mortar, and include water-soluble polymeric substances such as methyl cellulose (MC), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA), polyacrylamide, and polyethylene oxide (PEO). These prevent mortar from bouncing back or falling off, and improve the slipperiness of mortar when pumped. The content of the thickener is 0.01 parts by mass or more and 0.1 parts by mass or less relative to 100 parts by mass of cement. If it is 0.01 parts by mass or more, bleeding can be suppressed, and if it is 0.1 parts by mass or less, the flow value does not decrease and the compressive strength does not decrease. From the above viewpoints, the content of the thickener is more preferably 0.02 parts by mass or more and 0.08 parts by mass or less relative to 100 parts by mass of cement.

[0027] <Foaming agent> The foaming agent used in the present invention is used for the purpose of preventing the unhardened grout material from sinking or shrinking due to bleeding after application of the grout mortar. The foaming agent used in the present invention is not particularly limited as long as it generates gas after being mixed with water.

[0028] Examples of the foaming agent include oily substances such as vegetable oil and mineral oil. Other examples include metal powder and peroxide. Among them, aluminum powder is preferred in terms of the amount added and the effect, but the surface of aluminum powder is easily oxidized, and if it is covered with an oxide film, the reactivity decreases. Therefore, aluminum powder surface-treated with vegetable oil, mineral oil, stearic acid, or the like is preferred. Examples of the foaming agent include azo compounds, nitroso compounds, hydrazine derivatives, and other foaming agents that foam nitrogen gas under an alkaline atmosphere, as well as percarbonates such as sodium percarbonate, potassium percarbonate, and ammonium percarbonate, perborates such as sodium perborate and potassium perborate, permanganates such as sodium permanganate and potassium permanganate, and peroxides such as hydrogen peroxide. As the foaming agent used in the present invention, it is preferable to use aluminum powder that has been surface-treated with stearic acid or the like, since this has a large effect of suppressing subsidence.

[0029] The foaming agent may be a nitrogen gas foaming substance, which contains a compound that generates nitrogen gas by reacting with an alkali generated when cement is mixed with water, and may by-produce gases such as carbon monoxide, carbon dioxide, and ammonia. The nitrogen gas foaming substance used in the present invention is not particularly limited as long as it can be used to integrate the substance with a structure, to prevent the unhardened grout mortar from sinking or shrinking, and to improve the crack resistance when kept in a dry state.

[0030] The content of the foaming agent is preferably 0.001 parts by mass or more and 0.01 parts by mass or less, and more preferably 0.003 parts by mass or more and 0.007 parts by mass or less, relative to 100 parts by mass of cement. By making the content of the foaming agent equal to or more than the lower limit, a sufficient initial expansion effect can be imparted. In addition, by making the content of the foaming agent equal to or less than the upper limit, strength development is improved.

[0031] <Water reducing agent> The cement composition of the present invention contains a water reducing agent. The water reducing agent helps disperse each material and also plays a role in imparting fluidity to the mixed mortar. More specifically, it has a dispersing effect on cement and an air entraining effect, improving fluidity and promoting strength. Examples of the water reducing agent include naphthalene sulfonic acid-based water reducing agents, melamine sulfonic acid-based water reducing agents, lignin sulfonic acid-based water reducing agents, and polycarboxylic acid-based water reducing agents. In the present invention, in order to maintain fluidity sufficient for grouting even after 2 hours have passed since the mortar was mixed, it is preferable to use a melamine sulfonic acid-based water reducing agent in combination with a polycarboxylic acid-based water reducing agent.

[0032] The water reducing agent can be used in either powder or liquid form, but powder is preferred when used as a premix product. The content of the water reducing agent is preferably 0.1 parts by mass or more and 1 part by mass or less per 100 parts by mass of cement. If it is 0.1 parts by mass or more, it becomes easier to maintain the 2-hour flow, and if it is 1 part by mass or less, bubbles will not be generated, resulting in insufficient strength development, and there will be no significant delay in setting. From the above viewpoints, the content of the water reducing agent is more preferably 0.2 parts by mass or more and 0.7 parts by mass or less per 100 parts by mass of cement.

[0033] <Setting regulator> The cement composition of the present invention contains a set adjuster. There are no particular limitations on the set adjuster as long as it has an effect of retarding the setting of hydraulic cement. Specifically, for example, one or more selected from the group consisting of organic acids such as citric acid, gluconic acid, tartaric acid, malic acid, and the like, or salts thereof, boric acid, borates such as sodium borate, inorganic salts such as phosphates, alkali metal carbonates, alkali metal bicarbonates, and sugars, can be used. From the viewpoint of adjusting the hardening time and early strength development, it is more preferable that the setting regulator contains one or more selected from the group consisting of citric acid, citrates, tartaric acid, tartrates, and alkali metal carbonates, and it is particularly preferable to use an organic acid and an alkali metal carbonate in combination.

[0034] The content of the set regulator in the cement composition is preferably in the range of 0.1 parts by mass or more and 2 parts by mass or less per 100 parts by mass of cement. Within this range, it is possible to ensure a suitable pot life and short-term strength. From the above viewpoint, the content of the set regulator is more preferably in the range of 0.2 parts by mass or more and 1 part by mass or less per 100 parts by mass of cement.

[0035] [Cured body] The hardened product of the present invention is produced using the above-mentioned cement composition, and is a general term for hardened products of cement paste, mortar, and concrete. The cement paste according to the present invention is prepared by kneading the above-mentioned cement composition with water, and the content of water in the cement paste is about 10 to 40 mass%, preferably 20 to 30 mass%. The cement paste according to the present invention is useful as a gap filler because of its excellent fluidity and short-term strength development, and hardens over time to form a hardened body.

[0036] The mortar according to the present invention is obtained by further adding fine aggregate (sand) to the above cement paste. The fine aggregate is not particularly limited, and examples thereof include river sand, mountain sand, sea sand, lime sand, and silica sand. The content of the fine aggregate in the mortar is not particularly limited as long as it is within a range that does not impair the effects of the present invention, but is usually preferably 50 to 500 parts by mass, more preferably 100 to 450 parts by mass, and even more preferably 200 to 400 parts by mass, relative to 100 parts by mass of cement. The mortar according to the present invention has excellent fluidity and sufficient working life, and is excellent in terms of strength development in a short period of time, and therefore can be used in a wide range of civil engineering and construction applications, such as gap filling, self-leveling flooring materials, and lining materials.

[0037] Furthermore, the concrete according to the present invention is obtained by mixing coarse aggregate with the above mortar. The coarse aggregate is not particularly limited, but spherical aggregate is preferable in terms of not impairing fluidity. The maximum diameter of the coarse aggregate is not particularly limited, but is usually preferably 20 mm or less. If it is 20 mm or less, material separation does not occur and strength development is ensured. From the above viewpoint, it is more preferable that the maximum diameter of the coarse aggregate is 15 mm or less. The amount of coarse aggregate mixed is usually 100g per 1m of concrete composition. 3 When the amount of coarse aggregate is within 1000 kg, the fluidity is maintained. The concrete according to the present invention has a small calorific value and is therefore suitable for applications requiring a large thickness, such as machine foundations and concrete for filling under tracks. EXAMPLES

[0038] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0039] [Evaluation method] (1) Flow: Measured in accordance with JASS 15M-103. (2) Gel time: The gelation of the cement composition was measured by temperature. The cement compositions prepared in each Example and Comparative Example were placed in a cup, and the gel time (working time) was determined as the time when the temperature rose by 2°C from the mixing temperature. (3) Bleeding rate: According to JSCE-F 542, the bleeding rate was measured 10 minutes after the cement compositions prepared in each of the Examples and Comparative Examples were placed in a container. (4) Expansion and shrinkage rate: In accordance with JSCE-F 542, the cement compositions prepared in each of the Examples and Comparative Examples were placed in a form and then measured 24 hours later. (5) Compressive strength: Measured in accordance with JIS R 5201. The test specimen size was φ40mm × 160mm, and evaluation was performed on specimens with ages of 1 hour and 3 hours. (6) Crack resistance: In accordance with JHS432, the number of cracks that occurred after 28 days of material age and the presence or absence of cracks with a width of 0.05 mm or more were confirmed.

[0040] [Materials used] (a) Cement: Ordinary Portland cement, Blaine value: 3300 cm 2 / g, commercially available (b) Rapidly hardened wood (b-1) Rapid hardening material A: Amorphous, a mixture of calcium aluminate with the main component 12CaO 7Al2O3 and gypsum (calcium aluminate: 50% by mass, gypsum: 50% by mass), Blaine value 6000 cm 2 / g (b-2) Accelerated hardening material B: Amorphous, mixture of calcium aluminate with main component 12CaO 7Al2O3 and gypsum (calcium aluminate: 65% by mass, gypsum: 35% by mass), Blaine value 6000 cm 2 / g (b-3) Rapid hardening material C: Amorphous, a mixture of calcium aluminate with the main component 12CaO 7Al2O3 and gypsum (calcium aluminate: 80% by mass, gypsum: 20% by mass), Blaine value 6000 cm 2 / g (b-4) Rapid hardening material D: Amorphous, mixture of calcium aluminate with main component 12CaO 7Al2O3 and gypsum (calcium aluminate: 35 mass%, gypsum: 65 mass%), Blaine value 6000 cm 2 / g (b-5) Rapid hardening material E: Amorphous, mixture of calcium aluminate with main component 12CaO 7Al2O3 and gypsum (calcium aluminate: 20 mass%, gypsum: 80 mass%), Blaine value 6000 cm 2 / g (c) Silica fume: Silica fume containing zirconium oxide, with a zirconium oxide content of 5% and a BET specific surface area of ​​12 m 2 / g, pH 3.0, commercially available (d) Fiber: Vinylon fiber, fiber length 6 mm, fiber diameter 0.02 mm, commercially available (e) Clay minerals: Bentonite, commercially available (f) Thickener: Methylcellulose, commercially available (g) Foaming agent: Aluminum powder (surface-treated), commercially available (h) Water reducing agent: lignosulfonic acid-based water reducing agent, commercially available product (i) Setting agent: anhydrous citric acid, commercially available

[0041] Example 1 A cement composition was prepared consisting of 5 parts by mass of silica fume, 0.1 parts by mass of fiber, 0.15 parts by mass of clay mineral, 0.05 parts by mass of thickener, 0.005 parts by mass of foaming agent, 0.5 parts by mass of water reducing agent, 0.3 parts by mass of setting regulator, and a hardening agent shown in Table 1, per 100 parts by mass of cement. In this case, 35 parts by mass of mixing water was used per 100 parts by mass of cement composition. The flow, gel time, and compressive strength were measured at a temperature of 20°C. The results are shown in Table 1.

[0042] Examples 2 to 5 and Comparative Examples 1 to 5 Cement compositions were prepared in the same manner as in Example 1, except that the type and content of the hardening agent were changed as shown in Table 1. The results of evaluation in the same manner as in Example 1 are shown in Table 1.

[0043] [Table 1]

[0044] Example 6 A cement composition was prepared consisting of 30 parts by mass of hardening agent A per 100 parts by mass of cement, and silica fume, fiber, clay mineral, thickener, foaming agent, water reducing agent, and setting regulator shown in Table 2. In this case, 35 parts by mass of mixing water was used per 100 parts by mass of cement composition. The tests were performed at a temperature of 20°C to measure flow, gel time, bleeding rate, expansion / shrinkage rate, compressive strength, and crack resistance. The results are shown in Table 2.

[0045] Examples 7 to 25 and Comparative Examples 6 to 13 Cement compositions were prepared in the same manner as in Example 6, except that the blend ratio was changed as shown in Table 2. Various evaluation results are shown in Table 2.

[0046] [Table 2]

[0047] From the results in Table 1, the cement compositions using the hardening agents (hardening agents A, B, and D) containing 50 to 200 parts by mass of gypsum per 100 parts by mass of calcium aluminate showed good results in terms of flow and gel time, and also showed good results in terms of compressive strength. On the other hand, in Comparative Example 1, which did not use a hardening agent, the cement compositions did not harden even after 3 hours. In addition, when the content of the hardening agent is less than the range of the present invention, the gelation time is long and the compressive strength is low (Comparative Example 2).On the other hand, when the content of the hardening agent is more than the range of the present invention, the gelation time is short and sufficient usable time cannot be obtained (Comparative Example 3). Furthermore, when the gypsum content in the hardening agent is lower than the range of the present invention, the gelation time is short, sufficient pot life is not obtained, and the compressive strength is low (Comparative Example 4).On the other hand, when the gypsum content in the hardening agent is higher than the range of the present invention, the gelation time is long and the compressive strength is low (Comparative Example 5). Furthermore, it can be seen from the results in Table 2 that the cement composition of the present invention is a cement composition that is excellent in flow, gel time, bleeding rate, expansion and contraction rate, compressive strength, and crack resistance. [Industrial Applicability]

[0048] The cement admixture of the present invention significantly improves the salt damage resistance and rust prevention effect of concrete even under conditions where it is difficult to ensure a sufficient curing period, and therefore can be used widely in civil engineering and construction applications, contributing to extending the life of concrete structures.

Claims

1. A cement composition containing cement, a hardening agent, silica fume, fiber, a clay mineral, a thickener, a foaming agent, a water reducing agent, and a setting regulator, the hardening agent being contained in an amount of 10 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of the cement, the setting regulator being contained in an amount of 0.1 parts by mass or more and 1 part by mass or less relative to 100 parts by mass of the cement, the hardening agent being contained in calcium aluminate and gypsum, and the amount of the gypsum being 50 to 200 parts by mass relative to 100 parts by mass of the calcium aluminate. a content of the silica fume is 1 part by mass or more and 10 parts by mass or less per 100 parts by mass of the cement, a content of the clay mineral is 0.05 parts by mass or more and 0.3 parts by mass or less per 100 parts by mass of the cement, a content of the foaming agent is 0.001 parts by mass or more and 0.01 parts by mass or less per 100 parts by mass of the cement, a content of the water reducing agent is 0.1 parts by mass or more and 1 part by mass or less per 100 parts by mass of the cement, and the clay mineral is bentonite.

2. 2. The cement composition of claim 1, wherein said fibers are vinylon fibers.

3. The cement composition according to claim 1 or 2, wherein the content of the fiber is 0.02 parts by mass or more and 0.2 parts by mass or less relative to 100 parts by mass of the cement.

4. The cement composition according to any one of claims 1 to 3, wherein the content of the thickener is 0.01 parts by mass or more and 0.1 parts by mass or less with respect to 100 parts by mass of the cement.

5. A hardened body obtained by using the cement composition according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Supper quick-hardening high-fluidity cement composition and mortar or concrete using the same

    JP2007145652A

  • Method of constructing underwater column and cement hardening object for underwater application

    JP2009180020A

  • Quick-hardening PVA short fiber-blended mortar and quick-hardening high toughness FRC material using it

    JP2010013301A

  • Filling material for void part in embankment and filling construction method

    JP2014148424A

  • Super quick hardening cement mortar

    JP2017114734A